Politeness Strategies in Directive Questions: A Case Study of Jimmy Fallon on The Tonight Show Starring Jimmy Fallon - Sakut Anshori; Arbain Arbain; Abd. Rahman Zain (Borneo Educational Journal (Borju), 2026)
Abstract This study examines politeness strategies in directive utterances formed as questions by Jimmy Fallon, host of The Tonight Show Starring Jimmy Fallon. Utilizing Leech’s (1983) Politeness Principle, the research identifies and describes how politeness strategies are employed in interactions between Fallon and his guests. A qualitative descriptive approach is adopted, with data sourced from transcripts of 10 selected videos of The Tonight Show, chosen based on criteria such as popularity, guest prominence, and topic relevance. The analysis focuses on Leech’s six politeness maxims: Tact, Generosity, Approbation, Modesty, Agreement, and Sympathy. Findings reveal that Fallon consistently employs politeness strategies, particularly the Tact and Approbation Maxims. The Tact Maxim is manifested through polite language structures, including modal auxiliaries, indirect requests, and hedging devices, aimed at reducing the interlocutor’s communicative burden. The Approbation Maxim is reflected in explicit and implicit praise, as well as genuine interest in guests’ stories, enhancing their image and fostering interpersonal rapport. Additionally, the Agreement and Sympathy Maxims are utilized to maximize alignment and demonstrate empathy. The study concludes that Fallon’s use of politeness strategies not only mitigates potential threats to the guests’ “face” but also cultivates a positive, engaging, and entertaining communication environment. These findings contribute to pragmatic research in popular media, particularly in understanding politeness dynamics in entertainment talk shows. The practical implication underscores the significance of politeness strategies in public communication to foster effective, respectful, and enjoyable interactions.